Network Analysis and Boosting the Distribution to Local Consumers at Northern Senja, Norway with Potential Renewable Generation using Power Flow Control - Rochmann, Karl Henrik (UiT The Arctic University of Norway, 2022)
Renewable generation and power flow control are increasing its importance for power systems. The promising development in the technology increases the efficiency for transferring energy. With increasing consumption, remote locations benefit from close laying power production due to reduced transfer losses. In these recent years, energy storage system and local renewable energy production injected into the distribution grid has increased. The use of energy storage systems to supply active power has increased its relevance, especially battery energy storage systems. Senja's power systems suffers from limited transmission transfer capacity and increasing power demand is estimated in the following years. The northern part of Senja is heavily driven by the fishery industry, which needs to expand to meet the global seafood demand. In this thesis, the distribution network is simulated with power flow control injected with the distributed renewable generation. Through simulation, the solar and wind power production on the island is quantified. In addition is battery energy storage simulated to preform peak load shaving control to reduce the voltage variations for the local fishery industry. The combined effect of energy storage system and added power production impacts on the network performance is discovered. The potential energy resources show promising results. The wind power shows results of a capacity factor on over 50 %, which is higher than the average capacity factor in Europe. The implementation of power flow control with combined energy solutions show great results, especially for the battery energy storage. The peak load shaving can reduce the larger loads from 40-55 %, where the smaller loads peaks reduce with 5-10 %. The voltage drops are significantly reduced during the heavy load periods, including reduction in network losses. The local network gets the highest value with a combination of solar power and battery energy storage, rising the overall voltage of 2-3 %. The networks efficiency is increased and ...